Solid Tumor Microenvironment Can Harbor and Support Functional Properties of Memory T Cells - Sullivan, Peter M.; Reed, Steven James; Kalia, Vandana; Sarkar, Surojit (Frontiers in Immunology, 2021)
Robust T cell responses are crucial for effective anti-tumor responses and often dictate patient survival. However, in the context of solid tumors, both endogenous T cell responses and current adoptive T cell therapies are impeded by the immunosuppressive tumor microenvironment (TME). A multitude of inhibitory signals, suppressive immune cells, metabolites, hypoxic conditions and limiting nutrients are believed to render the TME non-conducive to sustaining productive T cell responses. In this study we conducted an in-depth phenotypic and functional comparison of tumor-specific T cells and tumor-nonspecific bystander memory T cells within the same TME. Using two distinct TCR transgenic and solid-tumor models, our data demonstrate that despite exposure to the same cell-extrinsic factors of the TME, the tumor-nonspecific bystander CD8 T cells retain the complete panoply of memory markers, and do not share the same exhaustive phenotype as tumor-reactive T cells. Compared to tumor-specific T cells, bystander memory CD8 T cells in the TME also retain functional effector cytokine production capabilities in response to ex vivo cognate antigenic stimulation. Consistent with these results, bystander memory T cells isolated from tumors showed enhanced recall responses to secondary bacterial challenge in a T cell transplant model. Importantly, the tumor-resident bystander memory cells could also efficiently utilize the available resources within the TME to elaborate in situ recall effector functions following intra-tumoral peptide antigen injection. Additionally, CRISPR-Cas9 gene deletion studies showed that CXCR3 was critical for the trafficking of both tumor antigen-specific and bystander memory T cells to solid tumors. Collectively, these findings that T cells can persist and retain their functionality in distinct solid tumor environments in the absence of cognate antigenic stimulation, support the notion that persistent antigenic signaling is the central driver of T cell exhaustion within the TME. These studies bear implications for programming more efficacious TCR- and CAR-T cells with augmented therapeutic efficacy and longevity through regulation of antigen and chemokine receptors.